Primary rhinoplasty at the time of unilateral cleft lip repair: A review and our protocol - Puthucode V Narayanan; Hirji Sorab Adenwalla (Wolters Kluwer Medknow Publications, 2015)
The cleft lip nasal deformity has been well described. However, for a long time, cleft surgeons feared that repair of the cleft lip nose at the time of primary repair would cause a growth disturbance especially of the nose. Hence the nasal deformity was not repaired until later. However, from the time of Blair and Barrett Brown, it has been shown that there are no deleterious growth effect from primary nasal interventions. At our centre the senior surgeon has performed primary nasal correction including septal respositioning from the late 1960s. There has been no deleterious growth effect and the overall appearance of the nose has actually improved. This is now well established through many objective studies. Hence it is now imperative that the deformity of the nose including the septum be addressed at the time of primary unilateral cleft lip repair.